2007
DOI: 10.1063/1.2710185
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced vortex-vortex switching in a nanopillar comprising two Co nano-rings

Abstract: We fabricated a current-perpendicular-to-plane pseudo-spin-valve nanopillar comprising a thick and a thin Co rings with deep submicron lateral sizes. The dc current can effectively induce the flux-closure vortex states in the rings with desired chiralities. Abrupt transitions between the vortex states are also realized by the dc current and detected with the giant magnetoresistance effect. Both Oersted field and spin-transfer torque are found important to the magnetic transitions, but the former is dominant. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The field is then lowered again, which nucleates a CW vortex in the top disc, according to the Oersted field of the negative applied current. Correspondingly, an OV-DV configuration is obtained at the point indicated by the yellow star 25 .…”
Section: Resultsmentioning
confidence: 99%
“…The field is then lowered again, which nucleates a CW vortex in the top disc, according to the Oersted field of the negative applied current. Correspondingly, an OV-DV configuration is obtained at the point indicated by the yellow star 25 .…”
Section: Resultsmentioning
confidence: 99%
“…16 More recently exchange bias ͑EB͒ has been explored in combination with a homogeneous external field to control reversal in Co/IrMn elliptical dots 17 and rings. 18 A combination of spin torque and Oersted field has been used to switch the chirality in pseudospin valve rings 19 and the spin torque effect alone has been predicted to switch the chirality in vortex-supporting spin-valve disks. 20 EB ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…As a source of unidirectional anisotropy, it has been shown that exchange bias ͑EB͒ can be used to control the reversal mechanisms in patterned nanomagnets. 17 While the majority of work on rings has been concerned with single layer, 16,18 or pseudospin valve structures, [19][20][21] there is limited reported work on EB bilayer rings [22][23][24] especially at low temperatures.…”
mentioning
confidence: 99%